2022
DOI: 10.3389/fonc.2022.835642
|View full text |Cite
|
Sign up to set email alerts
|

MET Inhibition Sensitizes Rhabdomyosarcoma Cells to NOTCH Signaling Suppression

Abstract: Rhabdomyosarcoma (RMS) is a pediatric myogenic soft tissue sarcoma. The Fusion-Positive (FP) subtype expresses the chimeric protein PAX3-FOXO1 (P3F) while the Fusion-Negative (FN) is devoid of any gene translocation. FP-RMS and metastatic FN-RMS are often unresponsive to conventional therapy. Therefore, novel therapeutic approaches are needed to halt tumor progression. NOTCH signaling has oncogenic functions in RMS and its pharmacologic inhibition through γ-secretase inhibitors blocks tumor growth in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…For migration assay, the cells were seeded at 100% of confluence on 96-well plate using Oris Cell Migration Assay Kit (#CMA1.101, Platypus Technologies, Madison, WI, United States) according to manufacturer instructions. Analysis of cell migration into the detection zone was performed after fixing and staining with Diff-Quick ® (460.053, Medion Diagnostic AG, Düdingen, Switzerland) as reported in ( Perrone et al, 2022 ). The images were taken using the Leica microscope Leica DMi8 with LAS X Navigator image acquisition software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For migration assay, the cells were seeded at 100% of confluence on 96-well plate using Oris Cell Migration Assay Kit (#CMA1.101, Platypus Technologies, Madison, WI, United States) according to manufacturer instructions. Analysis of cell migration into the detection zone was performed after fixing and staining with Diff-Quick ® (460.053, Medion Diagnostic AG, Düdingen, Switzerland) as reported in ( Perrone et al, 2022 ). The images were taken using the Leica microscope Leica DMi8 with LAS X Navigator image acquisition software.…”
Section: Methodsmentioning
confidence: 99%
“…For 3D tumor spheroids, RD and JR1 cells, transduced with pBABE and pSMOX retrovirus, were seeded in 100 µL of complete growth media on 96 Ultra-Low Attachment (#7007) (CORNING, New York, United States) well plates as previously described ( Perrone et al, 2022 ). Diameters of spheroids were evaluated every 24 h using Celigo image cytometer (Nexcelom Bioscience, Lawrence, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Transient RNA interference. Cells were transfected as described in 65 with siRNAs against either human SKP2 (SASI_Hs02_00340672s), mouse SKP2 (SASI_Mm02_00322740), human MYOD (custom: CUUGCCACAACGGACGACUU), human p27 (custom: ACGUAAACAGCUCGAAUUA), human p57 (custom: GAACCGGCUGGGAUUACGACUU) or with a non-targeting siRNA as control (SIC001) (Sigma-Aldrich, St Louis, MO, USA) (100 nM final concentration) using Oligofectamine (Invitrogen, Carlsbad, CA), according to the manufacturer's recommendations. Twenty-four hours later, the medium was replaced with fresh growth medium supplemented with 10% FBS, 1% Lglutamine and 1% penicillin-streptomycin, and the transfected cells were harvested at different time points.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that CSCs of several malignancies, also comprehending RMS, can resist ionizing radiation because of their peculiar metabolic status, associated with high expression of genes and pathways related to stem-like features, activated DNA repair mechanisms ( 232 ), and altered levels of free radical scavenger levels ( 233 ). Specifically, several studies have demonstrated the specific molecular pathways contributing to the CSC intrinsic radioresistance, such as PI3K/Akt/mTOR and NOTCH ones ( 234 237 ), which upregulates ROS scavenging enzymes ( 238 ). Thus, inhibiting NOTCH could be the efficient strategy to radiosensitize CSCs, bypassing their ability to detoxify from ROS.…”
Section: Mechanisms Of Radioresistance In Rmsmentioning
confidence: 99%